Tingkat Pengetahuan Terhadap Pubertas Pada Perubahan Fisik Remaja Putri - Sri Rezkiani Kas; Nurul Fajriah Istiqamah (Jurnal Keolahragaan JUARA, 2023)
Adolescence is the development achieved in adolescence and preparing for success in adulthood. As a transitional process, adolescence is marked by various physical, mental, intellectual, and social changes. Puberty or puberty is one of two periods in the life span marked by rapid growth and marked changes. The main problem experienced by adolescents is ignorance of the actions that must be taken in relation to the developments that are being experienced, especially the problem of adolescent knowledge about puberty and how adolescents behave in dealing with these changes. This study aims to determine the level of knowledge about puberty in the physical changes of female adolescents. This type of research uses a survey method. Based on the results of the analysis, it shows that there is a relationship between the level of knowledge and the physical changes during puberty of female adolescents. Researchers suggest that adolescents are more responsible for themselves and their surroundings by increasing knowledge of the physical changes during puberty